Inovasi Produk Kimia Ramah Lingkungan: Sabun Herbal dari Limbah Kulit Nanas sebagai Media Edukasi Siswa MAN 2 Pontianak - Weni Mandasari; Yulizar Prawiranti; Sofi Siti Shofiyah; Muftiah Yasi Dwi Wahyuni; Fitriyan Kurnia; Atika Wulandari Putri; Dodi; Yudith Evametha Vitranilla; Weny Ramadhania (Politeknik Piksi Ganesha Indonesia, 2025)
Many high school students perceive chemistry as a difficult subject and find it less relevant to daily life. To increase students' interest in chemistry studies, a Student Creativity Program (PKM) was conducted through the creation of herbal soap made from pineapple peel waste. Pineapple peel (Ananas comosus) was chosen because it contains bioactive compounds such as bromelain, flavonoids, tannins, and vitamin C, which have antibacterial and antioxidant properties. Through a project-based practical method, students from MAN 2 Pontianak were directly involved in the herbal soap-making process. The results of the activity showed an improvement in students' understanding of chemistry concepts and an increased interest in chemistry studies. Additionally, this activity supports environmental sustainability by utilizing organic waste. The implementation of practical learning methods has proven effective in enhancing critical thinking skills and fostering students' creativity in producing environmentally friendly products.